Moral Education Through Social Media in the Perspective of Islamic Digital Education - Salarian, Hossein; Hosseini, Seyyed Maryam (PT. Pusmedia Group Indonesia, 2025)
This study aims to examine social media usage strategies in moral education, assess the influence of digital content on character building, and offer a social media-based moral learning framework. This study uses a qualitative approach with a library research method through analysis of international scientific literature indexed by Google Scholar and Scopus (2018–2025). Literature selection was conducted using specific criteria: (1) published in reputable journals, (2) relevant to moral education and social media, (3) accessible in full text, and (4) written in English or Indonesian. A total of 35 articles were analyzed after the screening process. The results show that effective strategies for moral education through social media include creative packaging of Islamic content, strengthening interactivity, digital role models, forming virtual communities, and Islamic digital literacy. The findings also show that digital content has a dual effect: it can strengthen moral and prosocial values, but it also has the potential to weaken character if students are exposed to negative content without critical literacy. Furthermore, this study offers a social media-based moral learning framework that integrates Islamic content, interaction, community, role models, digital literacy, and the use of algorithms to strengthen moral values. This study provides theoretical contributions to the development of digital-based Islamic moral education, as well as practical contributions to designing learning strategies that are adaptive to the needs of the 21st century generation.